1979
DOI: 10.1111/j.2042-7158.1979.tb13510.x
|View full text |Cite
|
Sign up to set email alerts
|

Polycyanoacrylate nanocapsules as potential lysosomotropic carriers: preparation, morphological and sorptive properties

Abstract: w e have shown previously (Couvreur et a1 1977) that polyacrylamide nanocapsules are a new type of lysosomotropic carrier, but unfortunately they are unlikely to be digested by lysosomal enzymes. This article describes the preparation and the morphology of polyalkylcyanoacrylate nanocapsules since polyaanoacrylate may be biodegradable, as suggested by its us in surgery (Collins et al 1969;Heisterkamp et al 1969) and by its chemical properties (Cameron et al 1965; Leonard et a1 1966 a, b; Pani et al 1968).We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
164
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(168 citation statements)
references
References 4 publications
1
164
0
3
Order By: Relevance
“…Drug delivery applications of PACA nanoparticles have been broadly studied for 25 years due to advantages such as low toxicity and biodegradability [1,10]. BCA a member of alkyl cyanoacrylates group is a highly reactive monomer and anionic polymerization is one of the three mechanisms that can theoretically arise about this compound [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug delivery applications of PACA nanoparticles have been broadly studied for 25 years due to advantages such as low toxicity and biodegradability [1,10]. BCA a member of alkyl cyanoacrylates group is a highly reactive monomer and anionic polymerization is one of the three mechanisms that can theoretically arise about this compound [11].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly the simplicity of production was described by Couvreur [1]. He illustrated that submicron particle size can be prepared by scattering alkyl cyanoacrylate monomers in HCl solution at low pH containing an emulsifier.…”
Section: Introductionmentioning
confidence: 99%
“…Polybutylcyanoacrylate (PBCA) nanoparticles (NPs) are ideal carriers for delivery of this drug due to biodegradability and ability to change bio distribution of drugs. Additionally, they are easy to prepare and needless of any sort of purification [11][12][13][14]. Firstly, synthesis of such NPs was reported by Couvreur et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they are easy to prepare and needless of any sort of purification [11][12][13][14]. Firstly, synthesis of such NPs was reported by Couvreur et al [12]. Afterwards, several studies were reported around molecular weight distribution, toxicity, pharmacokinetics, bio distribution, stability and conjugation of different drugs [11,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The first albumin nanoparticles with a magnetic core were prepared shortly thereafter, but the method is very aggressive, leading to denaturation of the protein [73]. Around the same time, the first biodegradable acrylic nanoparticles made of poly(methylcyanoacrylate) and poly(ethylcyanoacrylate) [74] were developed. Similar compounds were later made with poly(n-butyl, isobutyl, n-hexyl and isohexyl-cyanoacrylates).…”
Section: Peptidic Nanoparticlesmentioning
confidence: 99%